A model to assess the relationship between management opportunism and auditor reactions: Simulation of financial restatements for a sample of Brazilian companies listed on the NYSE - Deaconu, Adela (2021)
Purpose – The objective of the paper is to investigate whether managers behave opportunistically by manipulating earnings and whether financial restatements, required by the auditors from the auditees, have the potential to decrease management opportunism. Design/methodology/approach – The empirical approach undertaken uses a self-constructed model in order to detect the influence of financial restatements on discretionary accruals and to observe possible earnings management practices, considering financial restatements as the explanatory variable. Findings – The values computed for discretionary accruals confirm the existence of earnings management and suggest possible management bias in accounting estimates and other accounting policies. Originality/value – This study provides a tool for overcoming deficiencies in relation to accounting estimates and other accounting policies in the auditing process, by assessing the relationship between management opportunism and auditors’ reactions using financial restatement requirements.